The draft for the 10th amendment of German competition law: Towards a new concept of "Outstanding relevance across markets"? - Oliver Budzinski; Sophia Gänßle; Annika Stöhr (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2020)
The ministerial proposal for a 10th amendment of the German competition law particularly addresses abuse control and seeks to tighten this pillar of competition policy against the background of the challenges from the digital economy. Next to extending the classic policy instruments of abuse control, the reform proposal suggests to introduce an additional and novel type of market power: the outstanding relevance across markets (ORAM). From an economic perspective, such an institution is interesting as it emphasizes non-horizontal and less direct anticompetitive abuses of market power. We review what type of cases could be subject to such a concept of systemic market power. Furthermore, we address the question whether merger control could also benefit from an ORAM-style conception.
Keywords: L40; K21; L41; L42; L49; K42; L81; L86; M21; 330; competition policy; abuse control; digital economy; market power; merger control; antitrust